Lexical Functions For Ants Based Semantic Analysis. - Schwab, Didier; Lafourcade, Mathieu (2007)
Semantic analysis (SA) is a central operation in natural language processing. We can consider it as the resolution of 5 problems: lexical ambiguity, references, prepositional attachments, interpretative paths and lexical functions instanciation.